Spider‐Inspired Electrohydraulic Actuators for Fast, Soft‐Actuated Joints. Issue 14 (29th May 2021) - Kellaris, Nicholas; Rothemund, Philipp; Zeng, Yi; Mitchell, Shane K.; Smith, Garrett M.; Jayaram, Kaushik; Keplinger, Christoph
Abstract: The impressive locomotion and manipulation capabilities of spiders have led to a host of bioinspired robotic designs aiming to reproduce their functionalities; however, current actuation mechanisms are deficient in either speed, force output, displacement, or efficiency. Here—using inspiration from the hydraulic mechanism used in spider legs—soft‐actuated joints are developed that use electrostatic forces to locally pressurize a hydraulic fluid, and cause flexion of a segmented structure. The result is a lightweight, low‐profile articulating mechanism capable of fast operation, high forces, and large displacement; these devices are termed spider‐inspired electrohydraulic soft‐actuated (SES) joints. SES joints with rotation angles up to 70°, blocked torques up to 70 mN m, and specific torques up to 21 N m kg −1 are demonstrated. SES joints demonstrate high speed operation, with measured roll‐off frequencies up to 24 Hz and specific power as high as 230 W kg −1 —similar to human muscle. The versatility of these devices is illustrated by combining SES joints to create a bidirectional joint, an artificial limb with independently addressable joints, and a compliant gripper. The lightweight, low‐profile design, and high performance of these devices, makes them well‐suited toward the development of articulating robotic systems that can rapidly maneuver. Abstract : Spider‐inspired electrohydraulic soft‐actuated (SES) joints provide compliant, electrohydraulic actuation for articulated robots. These joints exhibit fast actuation, high forces, and large displacements. This article characterizes the quasistatic and dynamic performance of SES joints experimentally and presents a model of their quasistatic behavior. The versatility of SES joints is demonstrated in a bidirectional joint, an artificial limb, and a compliant gripper.